2014
DOI: 10.1007/s12639-014-0583-7
|View full text |Cite
|
Sign up to set email alerts
|

Molecular approach for detecting early prepatent Schistosoma mansoni infection in Biomphalaria alexandrina snail host

Abstract: The present study aimed to evaluate a polymerase chain reaction (PCR) assay used for detection of Schistosoma mansoni infection in Biomphalaria alexandrina snails in early prepatent period and to compare between it and the ordinary detection methods (shedding and crushing). Biomphalaria alexandrina snails are best known for their role as intermediate hosts of S. mansoni. DNA was extracted from infected snails in addition to noninfected ''negative control'' (to optimized the efficiency of PCR reaction) and subj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 24 publications
(29 reference statements)
1
17
0
Order By: Relevance
“…Thus, the success of the assay is likely to depend both on snail abundance and infection prevalence. Importantly, all the locations where we identified schistosome-positive snails had much higher rates of infection than is typically observed, which can be around 2% [19], although we recognize that the PCR-based tests of snail infection may have revealed cases of prepatent infections in non-shedding snails [41].…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 96%
See 2 more Smart Citations
“…Thus, the success of the assay is likely to depend both on snail abundance and infection prevalence. Importantly, all the locations where we identified schistosome-positive snails had much higher rates of infection than is typically observed, which can be around 2% [19], although we recognize that the PCR-based tests of snail infection may have revealed cases of prepatent infections in non-shedding snails [41].…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 96%
“…Analyses were conducted using the qPCR approach as described above, although only presence or absence of an amplification is reported herein. We chose a PCR-based screening approach as it allowed us the opportunity to collect the samples in the field and screen the samples at a later date accurately for the focal species; however, the method can amplify individuals with prepatent infections that are not currently shedding cercariae [41]. To confirm the identity of PCR products amplified during these tissue assays, the PCR products from three Biomphalaria pfeifferi samples and three Bulinus globosus samples were Sanger sequenced.…”
Section: Environmental Dna From Aquarium Water Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study 23 , also in Pernambuco, showed that of the 64 verified breeding sites of B. straminea, 4 (6.25%) of them had snails releasing cercariae when exposed to artificial light, while the infection of 54 (84.4%) could only be determined by using a molecular biology technique. Other studies have also shown that the method of artificial photostimulation of snails is not able to detect infection in these animals 24 and that molecular techniques are more sensitive in detecting infection of snails by S. mansoni 21,[25][26][27] .…”
Section: Discussionmentioning
confidence: 99%
“…Microscopical examination of schistosome cercariae is then used to determine the infection status of snails [10][11][12], and the method requires considerable time, effort and expertise in the taxonomic identification of schistosome cercariae using microscopy. Alternatively, it is possible to test infection status of individual snails using molecular xenomonitoring tests for the presence of Schistosoma DNA in snail tissue using conventional endpoint PCR [13][14][15][16] or quantitative PCR [17,18]. While these methods requiring testing of individual snails have been very effective, they are limited by the need to test large numbers, as often only a small proportion of a total snail population are infected [19,20].…”
Section: Introductionmentioning
confidence: 99%